Financialisation Issues in a Post-Keynesian Stock-flow Consistent Model - Marc Lavoie (Intervention. European Journal of Economics and Economic Policies, 2008)
This paper presents a stock-flow consistent growth model which is set in the Post-Keynesian tradition. A key feature of the model, however, is that real government expenditures grow at a rate which is compatible over the long period with a constant rate of unemployment (at the "natural rate of growth"). The model incorporates a detailed description of the household, production, banking and government sectors. This paper focuses on changes in parameters that are tied with financialization. The effects on the following changes are examined: the target proportion of retained earnings to investment, the proportion of profits distributed as dividends, the propensity of households to hold equities, and the propensity of households to take new loans as a proportion of their personal income. There is also a short analysis of the impact of a change in the loan repayment ratio and in the loan default ratio.
Keywords: E12; O42; 330; financialization; growth; buffer stocks; disequilibria